Penyisihan Fosfat Pada Limbah Cair Laundry Dengan Biokoagulan Kitosan Cangkang Udang Windu - Evi Royana; Syarfi Daud; Edward Hs (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Chitosan is a Biocoagulant which is not poisonous, easy to degradable and polielectrolite. This research aims to know the the dose of coagulant and stirring speed in fosfat parameter removal to ward Laundry Liquid Waste and the result of the analyzed compared to PERMENLH/5/2014. This research was using Floculation and Sedimentation - Coagulation by using Chitosan from the Windu Shrimp Eggshell with different dose of coagulant and stirring speed to reduce the concentration of fosfat. The dose of coagulant is 150 mg/l, 175 mg/l, 200 mg/l and 225 mg/l and the stirring speed is 100 rpm, 125 rpm and 150 rpm in 1 minute and 40 rpm slow stirring in 20 minutes. The result showed that the optimum dose of Chitosan Biocoagulant 200 mg/l with the stirring speed 150 rpm with the removal efficiency 91,44%. The analysis results for fosfat have fulfill the laundry wastewater quality standards. Keywords: Chitosan, Fosfat, Flokulasi-Kuagulasi, Laundry Liquid wast.